Family system and deprivation of liberty: Narratives about the past, present and future - Politti, Mariana Elisa (2023)
This study aimed to explore and analyze the narratives about the past, present, and future of people with a family member deprived of liberty. Five women from Buenos Aires were interviewed regarding the matter, and the Thematic Analysis Method (Mieles Barrera et al., 2012) was used to categorize, analyze, describe, and interpret the speech. Those with an incarcerated family member have perceived various changes regarding their relationship with the inmate, the relationship with the justice/police, perception of family support, stigma/discrimination, dynamic family, and expectations/feelings. The departure of a family member on the grounds of incarceration requires a readjustment and rearrangement by their relatives. Analyzing the changes perceived by the family when having a member deprived of liberty provides a greater understanding of the subjective meaning of imprisonment for family members. Furthermore, it improves the visibility of an important theme in current society.